Nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystals / sulfur composite cathode material
Patent Information
- Application Number
- CN202311477277.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-08
AI Technical Summary
因此,这将导致放电容量低和容量快速衰减
[0022] This invention provides a nitrogen-doped molybdenum oxide/molybdenum carbide heterojunction nanocrystal/sulfur composite cathode material, comprising: nitrogen-doped transition metal molybdenum oxide/molybdenum carbide heterojunction nanocrystals, a three-dimensional porous graphene-like carbon material, and elemental sulfur; the nitrogen-doped transition metal molybdenum oxide/molybdenum carbide heterojunction nanocrystals have an octahedral structure; the nitrogen-doped transition metal molybdenum oxide/molybdenum carbide heterojunction nanocrystals are uniformly distributed on the three-dimensional porous graphene-like carbon material as a matrix and are composited with the elemental sulfur; the nitrogen-doped transition metal molybdenum oxide/molybdenum carbide heterojunction nanocrystals are obtained by mixing an organic polymer solution with a polyoxometalate solution and then heating at 800–1200°C. This invention can obtain a core-shell embedded octahedral nitrogen-doped transition metal molybdenum oxide/molybdenum carbide heterojunction nanocrystal/sulfur composite cathode material with high sulfur loading, uniform loading, uniform particle size, strong adsorption, and good conductivity. It can effectively suppress the shuttle effect of polysulfides, has high conductivity, and is particularly suitable as a sulfur carrier material for lithium-sulfur battery cathodes.
Smart Images

Figure CN117410468B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-sulfur battery cathode material technology, and in particular to a nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material. Background Technology
[0002] With the widespread application of lithium-ion batteries in portable electronics, electric vehicles, and plug-in hybrid electric vehicles, there is an urgent need to develop batteries with higher energy density. However, due to limitations in increasing the specific capacity of lithium-ion battery cathode materials, the energy density of lithium-ion batteries cannot be significantly increased further. At the same time, increasing the energy density by increasing the voltage plateau of the cathode material raises safety concerns. Shifting the cathode material from an "intercalation / deintercalation mechanism" to a "conversion reaction chemical mechanism" holds promise for materials with high specific capacity and specific energy. Elemental sulfur is one of the most promising cathode materials. Sulfur reacts completely with metallic lithium to form Li₂S; the battery reaction is S + 2Li = Li₂S, a two-electron reaction process that does not involve lithium-ion intercalation / deintercalation. Due to its low molecular weight, sulfur has a theoretical specific capacity as high as 1675 mAh / g (almost 10 times that of LiFePO₄), and a theoretical specific energy as high as 2600 Wh / kg. Furthermore, elemental sulfur is abundant in nature, low in toxicity, and inexpensive, making it a very attractive cathode material.
[0003] However, sulfur cathode materials also face some challenges, mainly including: (1) the dissolution of intermediate lithium polysulfides in the electrolyte. During cycling, the intermediate long-chain lithium polysulfides (Li2S4 to Li2S8) can easily dissolve in ether-based electrolytes. This phenomenon will lead to a continuous reduction in the active material in the electrode, some of which will still dissolve in the electrolyte at the end of discharge and cannot be deposited on the cathode surface. Therefore, this will lead to low discharge capacity and rapid capacity decay. The dissolution of lithium polysulfides is also the cause of the shuttle effect, resulting in a large amount of self-discharge, reduced coulombic efficiency and cycle performance, and irreversible capacity decay. (2) The low conductivity of elemental sulfur and discharge product lithium sulfide. The conductivity of S (5×10) -30 S / cm, 25℃), Li2S / Li2S2 conductivity (~10 S / cm, 25℃) -30 (3) The huge volume deformation of sulfur during the physicochemical process. From the orthorhombic α-S (ρ1=2.03g / cm), the utilization rate of sulfur is only about 50-70%. 3 The Li₂S structure is transformed into an antifluorite structure (ρ₂ = 1.66 g / cm³). 3 The large volume expansion damages the electrode structure and affects cycle stability. Summary of the Invention
[0004] To overcome the shortcomings of existing technologies, the first objective of this invention is to provide a core-shell embedded octahedral nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material with high sulfur loading, uniform loading, uniform particle size, strong adsorption, and good conductivity. This material effectively suppresses the shuttle effect of polysulfides, exhibits high conductivity, and is particularly suitable as a sulfur carrier material for lithium-sulfur battery cathodes.
[0005] Another objective of this invention is to provide a simple, low-cost method for preparing sulfur-loaded octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode materials for lithium-sulfur batteries, suitable for industrial production.
[0006] The third objective of this invention is to provide an application of an octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material in lithium-sulfur batteries. Using this material as a cathode material to prepare lithium-sulfur batteries has advantages such as high specific capacity, high energy density, and high cycle stability, which can greatly improve the cycle performance of lithium-sulfur batteries.
[0007] To achieve the above objectives, the present invention provides the following solution:
[0008] A nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material comprises: nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals, three-dimensional porous graphene-like carbon material, and elemental sulfur;
[0009] The nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal has a regular octahedral structure.
[0010] The nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals are uniformly distributed on the three-dimensional porous graphene-like carbon material as a matrix and are composited with the elemental sulfur; the nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals are obtained by mixing an organic polymer solution with a polyoxometalate solution at 800-1200℃.
[0011] Preferably, the diameter of the nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal is 500-1000 nm.
[0012] Preferably, the specific surface area of the nitrogen-doped transition metal molybdenum oxide-molybdenum carbide heterojunction nanocrystal is 100–500 m². 2 / g.
[0013] Preferably, the pore size of the micropores in the nitrogen-doped porous carbon matrix shell of the nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal is ≤2nm.
[0014] Preferably, the organic polymer comprises pyromellitic acid and L-glutamic acid.
[0015] Preferably, the solvent for the organic polymer solution is one or more of methanol, ethanol, or water.
[0016] Preferably, the solution concentration of the organic polymer is 5–20 g / L.
[0017] Preferably, the concentration of the polyoxometalate solution is 0.5–10 g / L.
[0018] A method for preparing a nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material, the preparation process is as follows:
[0019] An organic polymer solution is mixed with a polyoxometalate solution and stirred. The reaction is carried out under a protective atmosphere for 10–20 h. The temperature is increased to 800–1200 °C at a heating rate of 3–10 °C / min to obtain an octahedral nitrogen-doped molybdenum oxide-molybdenum carbide heterojunction. This heterojunction is then combined with elemental sulfur to obtain a composite cathode material. The octahedral nitrogen-doped molybdenum oxide-molybdenum carbide heterojunction is combined with elemental sulfur by ball milling, high-temperature thermal melting, in-situ liquid phase deposition, or liquid phase infiltration.
[0020] Application of nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material: The nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material is used as a cathode material for lithium-sulfur batteries.
[0021] According to specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0022] This invention provides a nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material, comprising: nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystals, a three-dimensional porous graphene-like carbon material, and elemental sulfur; the nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystals have an octahedral structure; the nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystals are uniformly distributed on the three-dimensional porous graphene-like carbon material as a matrix and are composited with the elemental sulfur; the nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystals are obtained by mixing an organic polymer solution with a polyoxometalate solution and then heating at 800–1200°C. This invention can obtain a core-shell embedded octahedral nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material with high sulfur loading, uniform loading, uniform particle size, strong adsorption, and good conductivity. It can effectively suppress the shuttle effect of polysulfides, has high conductivity, and is particularly suitable as a sulfur carrier material for lithium-sulfur battery cathodes. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 SEM image of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 1 of this invention.
[0025] Figure 2 The first discharge curve of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 1 of the present invention.
[0026] Figure 3 The graph shows the 100-cycle performance of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 1 of this invention at a current density of 0.5C.
[0027] Figure 4 The first discharge curve of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 2 of the present invention.
[0028] Figure 5 The graph shows the 100-cycle performance of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 2 of this invention at a current density of 0.5C.
[0029] Figure 6 The first discharge curve of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 3 of the present invention.
[0030] Figure 7 The graph shows the 100-cycle performance of the octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material obtained in Example 3 of this invention at a current density of 0.5C. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] The purpose of this invention is to provide a nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material, its preparation method, and its application.
[0033] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] Example 1
[0035] 3 g of phosphomolybdic acid hydrate, 0.753 g of L-glutamic acid, and 2 g of copper acetate monohydrate were added to 500 ml of deionized water and stirred continuously for 0.5 h. 1.4 g of 1,3,5-pyromellitic acid was added to 400 ml of anhydrous ethanol and ultrasonically dispersed. The pyromellitic acid ethanol solution was then added dropwise to the above mixture, stirred for 12 h, centrifuged, washed three times each with ethanol and water, and dried to obtain the precursor. Under an argon atmosphere, the precursor was placed in a tube furnace and heated to 800 °C at a heating rate of 5 °C / min, and held at that temperature for 3 h. The resulting product was an octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal. Octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals were mixed with sulfur powder at a mass ratio of 2:8 by high-speed ball milling for 2 hours. Then, under the protection of argon, the mixture was heated to 155℃ and held for 24 hours to obtain a graphene-like carbon material / sulfur composite cathode material.
[0036] The composite cathode material obtained in Example 1, conductive carbon black, and polyvinylidene fluoride (PVDF) were uniformly mixed in a mass ratio of 7:3:1 and dispersed in a certain mass of NMP to form a slurry (solid content of 80wt%). The slurry was then coated onto an aluminum foil current collector and vacuum dried at 60°C to obtain a lithium-sulfur battery cathode sheet.
[0037] Battery assembly and testing were performed as follows: The positive electrode was stamped into a 14mm diameter electrode sheet, with lithium metal as the negative electrode and a 1M LiTFSI / DOL:DME (1:1) electrolyte. CR2025 coin cells were assembled in an argon-filled glove box. Constant current charge-discharge tests were conducted at room temperature (25℃) with a current density of 0.5C (837mA / g), and the charge-discharge cutoff voltage was 1.7–2.8V. Figure 2 and Figure 3 As shown, the specific capacity of the first discharge cycle after stabilization is 816 mAh / g, and the specific capacity remains at 568 mAh / g after 100 cycles, maintaining a capacity retention rate of 69.6%.
[0038] Example 2
[0039] 3 g of phosphomolybdic acid hydrate, 0.753 g of L-glutamic acid, and 2 g of copper acetate monohydrate were added to 500 ml of deionized water and stirred continuously for 0.5 h. 1.4 g of 1,3,5-pyromellitic acid was added to 400 ml of anhydrous ethanol and ultrasonically dispersed. The pyromellitic acid ethanol solution was then added dropwise to the above mixture, stirred for 12 h, centrifuged, washed three times each with ethanol and water, and dried to obtain the precursor. Under an argon atmosphere, the precursor was placed in a tube furnace and heated to 900 °C at a heating rate of 5 °C / min, and held at that temperature for 3 h. The resulting product was an octahedral nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystal. Octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals were mixed with sulfur powder at a mass ratio of 2:8 by high-speed ball milling for 2 hours. Then, under the protection of argon, the mixture was heated to 155℃ and held for 24 hours to obtain a graphene-like carbon material / sulfur composite cathode material.
[0040] The composite cathode material obtained in Example 2, conductive carbon black, and polyvinylidene fluoride (PVDF) were uniformly mixed in a mass ratio of 7:3:1 and dispersed in a certain mass of NMP to form a slurry (solid content of 80wt%). The slurry was then coated onto an aluminum foil current collector and vacuum dried at 60°C to obtain a lithium-sulfur battery cathode sheet.
[0041] Battery assembly and testing were performed as follows: The positive electrode was stamped into a 14mm diameter electrode sheet, with lithium metal as the negative electrode and a 1M LiTFSI / DOL:DME (1:1) electrolyte. CR2025 coin cells were assembled in an argon-filled glove box. Constant current charge-discharge tests were conducted at room temperature (25℃) with a current density of 0.5C (837mA / g), and the charge-discharge cutoff voltage was 1.7–2.8V. Figure 4 and Figure 5 As shown, the specific capacity of the first discharge cycle after stabilization is 596 mAh / g, and the specific capacity remains at 410 mAh / g after 100 cycles, maintaining a capacity retention rate of 68.8%.
[0042] Example 3
[0043] 3 g of phosphomolybdic acid hydrate, 0.753 g of L-glutamic acid, and 2 g of copper acetate monohydrate were added to 500 ml of deionized water and stirred continuously for 0.5 h. 1.4 g of 1,3,5-pyromellitic acid was added to 400 ml of anhydrous ethanol and ultrasonically dispersed. The pyromellitic acid ethanol solution was then added dropwise to the above mixture, stirred for 12 h, centrifuged, washed three times each with ethanol and water, and dried to obtain the precursor. Under an argon atmosphere, the precursor was placed in a tube furnace and heated to 1000 °C at a heating rate of 5 °C / min, and held at that temperature for 3 h. The resulting product was an octahedral nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterostructure nanocrystal. Octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals were mixed with sulfur powder at a mass ratio of 2:8 by high-speed ball milling for 2 hours. Then, under the protection of argon, the mixture was heated to 155℃ and held for 24 hours to obtain a graphene-like carbon material / sulfur composite cathode material.
[0044] The composite cathode material obtained in Example 3, conductive carbon black, and polyvinylidene fluoride (PVDF) were uniformly mixed in a mass ratio of 7:3:1 and dispersed in a certain mass of NMP to form a slurry (solid content of 80wt%). The slurry was then coated onto an aluminum foil current collector and vacuum dried at 60°C to obtain a lithium-sulfur battery cathode sheet.
[0045] Battery assembly and testing were performed as follows: The positive electrode was stamped into a 14mm diameter electrode sheet, with lithium metal as the negative electrode and a 1M LiTFSI / DOL:DME (1:1) electrolyte. CR2025 coin cells were assembled in an argon-filled glove box. Constant current charge-discharge tests were conducted at room temperature (25℃) with a current density of 0.5C (837mA / g), and the charge-discharge cutoff voltage was 1.7–2.8V. Figure 6 and Figure 7 As shown, the specific capacity of the first discharge cycle after stabilization was 498 mAh / g, and the specific capacity remained at 335 mAh / g after 100 cycles, maintaining a capacity retention rate of 67.2%.
[0046] The beneficial effects of this invention are as follows:
[0047] (1) The octahedral nitrogen-doped transition metal molybdenum oxide / molybdenum carbide heterojunction nanocrystal of the present invention has a porous crystal structure with a periodic network structure formed by the self-assembly of transition metal ions and organic ligands. The preparation of its heterostructure significantly improves the adsorption-catalytic performance because the heterostructure interface generates highly active sites (dislocations or defects), and the combination of active sites for various basic steps allows for acceleration of the entire redox reaction. Furthermore, the high degree of graphitization is beneficial for improving internal and external conductivity, thereby increasing sulfur utilization. Simultaneously, the nitrogen-doped porous carbon matrix has abundant micro- and nano-pore structures and a large surface area, which is beneficial for storing sulfur and suppressing polysulfide shuttle. These characteristics make it particularly suitable for use as a sulfur carrier in lithium-sulfur batteries.
[0048] (2) The present invention uses organic polymers and transition metal salts to prepare octahedral nitrogen-doped transition metal molybdenum oxide and molybdenum carbide heterojunction nanocrystals by mixing and stirring and high-temperature pyrolysis. The method is simple, has a short process, low cost and is conducive to industrial production.
[0049] (3) The present invention combines octahedral nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals with elemental sulfur to obtain a thin-walled localized graphitized porous carbon / sulfur composite cathode material with high sulfur loading (sulfur content up to 80 wt.%), which can effectively suppress the dissolution of polysulfides in the electrolyte, high utilization rate of active material sulfur, and high specific capacity, which can greatly improve the cycle stability of lithium-sulfur batteries.
[0050] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0051] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. Furthermore, those skilled in the art will recognize that, based on the ideas of the present invention, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material, characterized in that, include: Nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals, three-dimensional porous graphene-like carbon materials, and elemental sulfur; The nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal has a regular octahedral structure. The nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals are uniformly distributed on the three-dimensional porous graphene-like carbon material as a matrix and are composited with the elemental sulfur; the nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals are obtained by mixing an organic polymer solution with a polyoxometalate solution at 800-1200℃.
2. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to claim 1, characterized in that, The diameter of the nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystals is 500–1000 nm.
3. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to claim 1, characterized in that, The nitrogen-doped transition metal molybdenum oxide and molybdenum carbide heterojunction nanocrystals have a specific surface area of 100–500 m². 2 / g.
4. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to claim 1, characterized in that, The pore size of the micropores in the nitrogen-doped porous carbon matrix shell of the nitrogen-doped transition metal molybdenum oxide molybdenum carbide heterojunction nanocrystal is ≤2nm.
5. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to claim 1, characterized in that, The organic polymers include pyromellitic acid and L-glutamic acid.
6. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to any one of claims 1 or 2, characterized in that, The solvent for the organic polymer solution is one or more of methanol, ethanol, or water.
7. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to any one of claims 1-3, characterized in that, The concentration of the organic polymer solution is 5–20 g / L.
8. The nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to claim 1, characterized in that, The concentration of the polyoxometalate solution is 0.5–10 g / L.
9. A method for preparing the nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material as described in claim 1, characterized in that, The preparation process of the nitrogen-doped transition metal molybdenum oxide and molybdenum carbide heterojunction nanocrystals is as follows: An organic polymer solution is mixed with a polyoxometalate solution and stirred. The reaction is carried out under a protective atmosphere for 10–20 h. The temperature is increased to 800–1200 °C at a heating rate of 3–10 °C / min to obtain an octahedral nitrogen-doped molybdenum oxide-molybdenum carbide heterojunction. This heterojunction is then combined with elemental sulfur to obtain a composite cathode material. The octahedral nitrogen-doped molybdenum oxide-molybdenum carbide heterojunction is combined with elemental sulfur by ball milling, high-temperature thermal melting, in-situ liquid phase deposition, or liquid phase infiltration.
10. The application of the nitrogen-doped molybdenum oxide / molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material according to claim 1, characterized in that, The nitrogen-doped molybdenum oxide molybdenum carbide heterojunction nanocrystal / sulfur composite cathode material is used as a cathode material for lithium-sulfur batteries.
Citation Information
Patent Citations
Water electrolysis hydrogen evolution catalyst and preparation and application thereof
CN114045527A
Nitrogen-doped multi-component metal sulfide heterostructure nano material
CN116159584A